2019
DOI: 10.1016/j.healthpol.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Health service accreditation stimulating change in clinical care and human resource management processes: A study of 311 Australian hospitals

Abstract: Highlights Health service accreditation stimulating change in clinical care and human resource management processes: a study of 311 Australian hospitals Health service accreditation stimulating change in clinical care and human resource management processes: a study of 311 Australian hospitals Abstract Objective: This study aimed to establish whether longitudinal participation in an accreditation program is translated into improvement in continuity of quality patient care and human resource management (HRM) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…While the impact and outcome of healthcare accreditation remain debatable, the growth of such programs has accelerated significantly over the past decades (Nicklin et al, 2017). In addition, over 70 countries have employed such accreditation programs in their healthcare organizations, including developing countries such as the United Arab Emirates (Greenfield and Braithwaite, 2008;Devkaran and O'Farrell, 2015;Greenfield et al, 2019). While healthcare accreditation might be appealing to managers and stakeholders, many have argued that accreditation is a demanding activity, which increases workload and stress levels among workers (Touati and Pomey, 2009;Elkins et al, 2010;El-Jardali et al, 2014;Kousgaard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the impact and outcome of healthcare accreditation remain debatable, the growth of such programs has accelerated significantly over the past decades (Nicklin et al, 2017). In addition, over 70 countries have employed such accreditation programs in their healthcare organizations, including developing countries such as the United Arab Emirates (Greenfield and Braithwaite, 2008;Devkaran and O'Farrell, 2015;Greenfield et al, 2019). While healthcare accreditation might be appealing to managers and stakeholders, many have argued that accreditation is a demanding activity, which increases workload and stress levels among workers (Touati and Pomey, 2009;Elkins et al, 2010;El-Jardali et al, 2014;Kousgaard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Benefits from accreditation seems to be linked to the motivation for the activities involved in the process [ 18 ]. Recent research from Australian hospitals has demonstrated that accreditation supports continuous and systematic quality improvement [ 19 ]. However, little is known in healthcare about the approach and methods that external assessment bodies use in their assessment and verification processes, such as auditor’s role repertoire, auditor’s conduct (e.g., inspection or guidance) and assessment practice [ 4 , 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…90 Performance data from two cohort studies suggest that hospital size and type did not predict effects of accreditation 91 ; however, lower performing hospitals improved at a greater rate than moderate and higher performing hospitals. 92 Two case studies indicate that degree of improvement can depend on improvement capability of the inspected organisation, 43 and that accreditation can be easier to implement in smaller facilities. 76 Creation of networks, and improved communications Qualitative data indicate that inspections can contribute to improved teamwork and communication within existing networks in the sense that these can become more focused around how the organisation delivers clinical care.…”
Section: External Incentivesmentioning
confidence: 99%